Evolving Real-Time Audio Description Solutions for Visually Impaired Users: From HMD to Mobile Platforms - Mauricio, Claudio Roberto M.; Domingues, Gustavo Camargo; Vieira, Vitor Luiz Binsfeld; Padua, Ivã; Peres, Fabiana Frata Furlan; Teixeira, João Marcelo X. N. (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2024: Anais do XXI Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2024.245674, 2024)
Assistive technologies for visually impaired individuals are crucial for enhancing their independence and quality of life. This paper discusses the evolution of a real-time audio description solution for visually impaired users from using a Head-Mounted Display to a more mobile and affordable platform utilizing a Raspberry Pi Zero 2W with a camera and battery. This second solution offers the same level of performance as the first, with added advantages of lower cost and enhanced mobility. The new system has been evaluated by the same visually impaired user from before, who provided valuable feedback on the user experience.